Situational Forgiveness in Cancer Patients - Clarissa Maldini Henderina Bisinglasi; Rizky Pradita Manafe; Zerlinda C. A. Sanam; Marleny P. Panis (Universitas Nusa Cendana, 2026)
Introduction Cancer causes not only physical symptoms but also psychological distress. Situational forgiveness may help patients cope with emotional burdens, yet little is known about this process among Indonesian cancer patients. Aim This study explored the process and influencing factors of situational forgiveness among cancer patients using a photovoice approach. A qualitative Participatory Action Research design with photovoice was conducted among cancer patients. Result Thematic analysis identified four themes: causes of suffering, denial, coping strategies (social support and religiosity), and forgiveness through reconstruction, gratitude, spiritual beliefs, and healthy lifestyle changes. Conclusion Forgiveness developed gradually from denial toward acceptance, supported by family, community, and faith. Situational forgiveness is a dynamic psychological process shaped by emotional, social, spiritual, and cultural factors. Strengthening family, community, and spiritual support may promote psychological well-being among cancer patients.